Inflammation-Modulating Hydrogels for Osteoarthritis Cartilage Tissue Engineering - Rachel H. Koh; Yinji Jin; Jisoo Kim; Nathaniel S. Hwang (Cells, 2020)
Osteoarthritis (OA) is the most common form of the joint disease associated with age, obesity, and traumatic injury. It is a disabling degenerative disease that affects synovial joints and leads to cartilage deterioration. Despite the prevalence of this disease, the understanding of OA pathophysiology is still incomplete. However, the onset and progression of OA are heavily associated with the inflammation of the joint. Therefore, studies on OA treatment have sought to intra-articularly deliver anti-inflammatory drugs, proteins, genes, or cells to locally control inflammation in OA joints. These therapeutics have been delivered alone or increasingly, in delivery vehicles for sustained release. The use of hydrogels in OA treatment can extend beyond the delivery of anti-inflammatory components to have inherent immunomodulatory function via regulating immune cell polarization and activity. Currently, such immunomodulatory biomaterials are being developed for other applications, which can be translated into OA therapy. Moreover, anabolic and proliferative levels of OA chondrocytes are low, except initially, when chondrocytes temporarily increase anabolism and proliferation in response to structural changes in their extracellular environment. Therefore, treatments need to restore matrix protein synthesis and proliferation to healthy levels to reverse OA-induced damage. In conjugation with injectable and/or adhesive hydrogels that promote cartilage tissue regeneration, immunomodulatory tissue engineering solutions will have robust potential in OA treatment. This review describes the disease, its current and future immunomodulatory therapies as well as cartilage-regenerative injectable and adhesive hydrogels.